Factors related to improvement of symptoms, function, and caregiver burden in Chinese patients with schizophrenia after switching to paliperidone palmitate once-monthly from oral antipsychotics - Li N (Dove Medical Press, 2018)
Nan Li,1 Yu Feng,2 Huafei Lu,3 Shang Li Cai,3 Jianmin Zhuo,4 Tianmei Si,5,6 Lili Zhang3 1Research Center of Clinical Epidemiology, Peking University Third Hospital, Beijing, People’s Republic of China; 2Regional Medical Affairs, Janssen Pharmaceutical Companies of Johnson and Johnson, Singapore; 3Medical Affairs, Xian Janssen Pharmaceutical Ltd, Beijing, People’s Republic of China; 4Department of Statistics, Janssen China Research and Development, Shanghai, People’s Republic of China; 5National Clinical Research Center for Mental Disorders and The Key Laboratory of Mental Health, Ministry of Health (Peking University), Beijing, People’s Republic of China; 6Peking University Institute of Mental Health (The Sixth Hospital), Beijing, People’s Republic of China Background: Paliperidone palmitate once-monthly (PP1M) demonstrated symptomatic and functional remission in patients with schizophrenia. This post hoc analysis aimed to identify factors associated with improved clinical outcomes in patients switching to PP1M (75–150 mg eq.).Methods: The improved patient outcomes were observed as Positive and Negative Symptom Scale (PANSS, symptoms) score <70:66.7% (407/610), Personal and Social Performance (PSP, function) score >70:34.3% (199/581), and Involvement Evaluation Questionnaire (IEQ, caregiver burden) reduction ≥6:50.2% (270/538). Independent variables including demographics, disease duration, employment status, and clinical scores were screened individually using a univariate analysis and subsequently, variables (cutoff p<0.15) were analyzed using a multivariate regression analysis for association with better clinical outcomes at week 13.Results: The factors significantly associated with favorable clinical outcomes were reduction in PANSS at week 5 (odds ratio [OR]=1.14, 95% CI=1.11–1.17) with symptom reduction; baseline PSP total score (OR=1.07, 95% CI=1.05–1.10), PSP change at week 5 (OR=1.07, 95% CI=1.05–1.10), PANSS reduction at week 5 (OR=1.06, 95% CI=1.03–1.08) with functional improvement, reduction in PANSS at week 5 (OR=1.02, 95% CI=1.01–1.03), and total IEQ score at baseline (OR=1.09, 95% CI=1.07–1.11) with caregiver burden reduction.Conclusion: Thus, symptom and functional improvements with caregiver burden reduction were observed in patients, and PANSS reduction at week 5 was commonly associated with favorable outcomes. Keywords: caregiver burden, clinical outcomes, post hoc analyses, psychosocial function, remission